Total hip replacement for a case of spondyloepiphyseal dysplasia tarda with premature hip arthritis: two case reports (Indian Journal of Case Reports, 2025)
Spondyloepiphyseal dysplasia (SED) tarda is an extremely uncommon form of skeletal dysplasia, characterized by congenital dwarfism with a short trunk and epiphyseal dysplasia in the long bones and vertebral bodies. It is an X-linked recessive condition not evident at birth, the usual age of presentation is after the first decade of life. These patients commonly present with short trunk and arm spans significantly greater than height and premature hip arthritis. In this article, we present two short-statured male patients of age 28 years with early hip arthritis diagnosed to be SED Tarda with clinical examination and radiological findings, who underwent primary hybrid total hip replacement of dysplastic hip with excellent post-operative functional outcome.